Climate and environmental drivers of berry productivity from the forest-tundra ecotone to the high Arctic in Canada - Boulanger-Lapointe, N.; Henry, G. H. R.; Lévesque, E.; Cuerrier, A.; Desrosiers, S.; Gérin-Lajoie, J.; Hermanutz, L.; Collier, L. S. (Arctic Science, 2020)
Abstract Berry shrubs are found across the circumpolar North where they are an important source of food for people and animals. However, the environmental controls on berry productivity in these regions is poorly understood. This study presents the results of an ongoing berry productivity monitoring program for Empetrum nigrum L., Vaccinium uliginosum L., and Vaccinium vitis-idaea L. from the forest–tundra ecotone to the high Arctic in Canada. Berry productivity was the highest recorded for these species with up to 119 berries/m2 (E. nigrum) and 661 berries/m2 (V. uliginosum) measured at one plot in Pangnirtung. On average, berry productivity for E. nigrum and V. uliginosum was higher toward the northern edge of the species distribution range. The climate variables important for the productivity of V. uliginosum in high Arctic sites were closely associated with the onset of the growing season and water availability during the growing season, whereas those important in the low Arctic sites reflected conditions during the growing season. None of the climate variables used were associated with the productivity of E. nigrum and V. vitis-idaea, likely due to complex responses and length of the time-series, thus highlighting the importance of continued monitoring in partnership with northern people and institutions. Résumé Les arbustes producteurs de baies sont répandus au Nord du cercle polaire où ils constituent une source importante de nourriture pour les humains et les animaux. Malgré leur importance écologique, on connaît peu de choses quant à l’influence des facteurs environnementaux sur la productivité en fruits de ces espèces. Cette étude présente les résultats d’un programme de suivi à long terme d’Empetrum nigrum L., Vaccinium uliginosum L., et Vaccinium vitis-idaea L. depuis l’écotone forêt–toundra jusque dans le haut Arctique au Canada. La plus haute productivité en fruits connue pour ces espèces a été mesurée à Pangnirtung avec des valeurs pouvant atteindre jusqu’à 119 fruits/m2 (E. nigrum) et 661 ...